PENERAPAN METODE LATIHAN KETERAMPILAN PSIKOLOGIS UNTUK MENINGKATAN KINERJA WASIT DALAM MEMIMPIN PERTANDINGAN SEPAKBOLA - Mudian, Deni (2014)
The purpose of this study is to know the whether the application of psychological skills training methods such as relaxation exercises, imagery, and relaxation-imagery can provide a significant effect on performance improvement in leading the football match referee. Research conducted on the referee PSSI Subang, and methods in research is an experimental method to the design of the two control one experimental group pretest-posttest design. Instruments to collect in this study is the referee assessment form. This assessment form is an official form issued by FIFA and is used by the PSSI to measure the performance of the referee in a football game lead. The conclusion of this study is a method of psychological skills training such as relaxation exercises significant influence on the performance of the referee in a football game lead, psychological skills training methods such as imagery exercises significant influence on the performance of the referee in a football game lead, psychological skills training methods such as relaxation exercises -imagery significant influence on the performance of the referee in a football game lead, and psychological skills training methods of relaxation-imagery more significant influence on the performance of the referee in a football game lead. Suggestions for PSSI and the referee commission, in order to provide psychological skills training in every session, because the psychological skills training is crucial to improve the performance of the referee in a football game lead